Strong Quantum Confinement Effect in the Optical Properties of Ultrathin α‐In2Se3. Issue 12 (16th August 2016) - Quereda, Jorge; Biele, Robert; Rubio‐Bollinger, Gabino; Agraït, Nicolás; D'Agosta, Roberto; Castellanos‐Gomez, Andres
Abstract : The effect of quantum confinement in the optical absorption spectra of atomically thin α‐In2 Se3 crystals is studied, observing a huge thickness‐dependent shift in the optical band gap of exfoliated α‐In2 Se3 flakes. The band gap variation reported here is among the largest found in semiconductor crystals and spans a region of the near‐UV spectrum uncovered by other 2D semiconductors.